Secretion of Na+, K+ and fluid by the Malpighian (renal) tubule of the larval cabbage looper Trichoplusia ni (Lepidoptera: Noctuidae). (November 2015) - Ruiz-Sanchez, Esau; O'Donnell, Michael J.; Donini, Andrew
Graphical abstract: Highlights: Fluid is secreted by the upper (distal) regions of the Malpighian tubules of larval Trichoplusia ni . Upper regions of the tubules secrete K +, whereas lower regions reabsorb it. Fluid secretion rate decreased after addition of bafilomycin A1, amiloride or bumetanide to the bathing saline. When fluid secretion is stimulated by cAMP or 5-HT, the concentration of K + in the secreted fluid decreases. Transepithelial potential and pH of the secreted fluid do not change in response to cAMP or 5-HT. Abstract: The Malpighian (renal) tubules play important roles in ionic and osmotic homeostasis in insects. In Lepidoptera, the Malpighian tubules are structurally regionalized and the concentration of Na + and K + in the secreted fluid varies depending on the segment of tubule analyzed. In this work, we have characterized fluid and ion (Na +, K +, H + ) transport by tubules of the larval stage of the cabbage looper Trichoplusia ni ; we have also evaluated the effects of fluid secretion inhibitors and stimulants on fluid and ion transport. Ramsay assays showed that fluid was secreted by the iliac plexus but not by the yellow and white regions of the tubule. K + and Na + were secreted by the distal iliac plexus (DIP) and K + was reabsorbed in downstream regions. The fluid secretion rate decreased > 50% after 25 μM bafilomycin A1, 500 μM amiloride or 50 μM bumetanide was added to the bath. The concentration of K + in the secreted fluid did not change, whereas the concentration of Na + in the secreted fluid decreased significantly when tubules were exposed to bafilomycin A1 or amiloride. Addition of 500 μM cAMP or 1 μM 5-HT to the bath stimulated fluid secretion and resulted in a decrease in K + concentration in the secreted fluid. An increase in Na + concentration in the secreted fluid was observed only in cAMP-stimulated tubules. Secreted fluid pH and the transepithelial electrical potential (TEP) did not change when tubules were stimulated. Taken together, our results show that the secretion of fluid is carried out by the upper regions (DIP) in T. ni Malpighian tubules. Upper regions of the tubules secrete K +, whereas lower regions reabsorb it. Stimulation of fluid secretion is correlated with a decrease in the K + /Na + ratio.